Sociology - Giddens, Anthony; Sutton, Philip W. (Polity Press, 2013)
An introduction to the discipline of sociology: the key theories and ideas, core thinkers and theorists, and an overview of the central topics and issues sociologists study - all with an eye to helping students develop a sociological way of thinking about, interrogating, and analysing the world and our social interactions within it.